Survival Analysis up to 8 Years of 304 Anatomical-Contour Implant-Supported Zirconia Crowns Fabricated with a Fully Digital Cast-Free Workflow and Directly Screwed on External Hexagonal Implant Connections Without the Interposition of a Ti-Base: A Multicentric Retrospective Study - Schmitz, Johannes H.; Valenti, Marco; Valenti, Alessandro; Cortellini, Davide; Canale, Angelo (International Journal of Oral & Maxillofacial Implants)
Purpose: To evaluate the real-life clinical results of monolithic zirconia (Zr) screw-retained crowns without the interposition of a titanium base (Ti-base) on external hex implants fabricated from intraoral scans and a cast-free approach in private practice. Materials and Methods: Single external hex implants were restored with monolithic Zr crowns without the interposition of a Ti-base. The crowns were directly screwed on the external hex implant connections with a cast-free, fully digital workflow. Data were analyzed using descriptive statistics and the Kaplan-Meier test. Between September 2022 and March 2023, the California Dental Association's modified criteria were adopted for the present clinical evaluation after recalling all patients. Results: A total of 304 single-tooth restorations in the maxillary and mandibular posterior regions were fabricated between July 2014 and July 2022 in 252 patients (120 males and 132 females, mean age: 53.6 years; SD: 23.3). Seven crowns were excluded because of patient dropout. The most common minor technical complications were screw loosening (three crowns) and loss of the screw access hole filling (three crowns). There were four failures, including two implant failures with mobility and two fractured crowns. No screw or implant fractures were recorded. The overall cumulative survival rate was 98.6%, and the average success rate (crowns experiencing no failures or complications) was 96.0%. The mean overall survival time was 101.3 months (standard error: 0.847; 95% CI for the mean, 99.67-102.99). The overall survival probability was 87.9% up to 97 months. Conclusions: With careful case selection and a comprehensive periodontal maintenance program, single crowns that were directly screwed onto an external hex platform showed excellent survival and success rates that were comparable to available data regarding single crowns with a Ti-base prosthetic interface.